2022
DOI: 10.1002/app.52653
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the dissolving system of ultra‐high molecular weight polyethylene to enhance the high‐strength and high‐modulus properties of resultant fibers

Abstract: The molecular weight loss of ultra‐high molecular weight polyethylene (UHMWPE) fibers is extremely serious in comparison with raw materials due to the high temperature and strong shearing during dissolving process. In this study, decalin was introduced as preswelling solvent and the dissolving system was regulated to improve the solubility of UHMWPE in paraffin oil without severe degradation so as to prepare UHMWPE fibers with high molecular weight retention and low entanglement. UHMWPE was preswelling in deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In our previous work, 26 it was found that the obtained fibers possessed the best high-strength and high-modulus properties when UHMWPE was swollen in 300 wt% decalin at 100 C for 10 min. A certain amount of OO (10, 20, 30, and 40 wt% of UHMWPE powder) was added to participate in the swelling of UHMWPE in decalin at 108 C under mechanical stirring on the basis of above swelling process.…”
Section: Sample Preparationmentioning
confidence: 90%
See 2 more Smart Citations
“…In our previous work, 26 it was found that the obtained fibers possessed the best high-strength and high-modulus properties when UHMWPE was swollen in 300 wt% decalin at 100 C for 10 min. A certain amount of OO (10, 20, 30, and 40 wt% of UHMWPE powder) was added to participate in the swelling of UHMWPE in decalin at 108 C under mechanical stirring on the basis of above swelling process.…”
Section: Sample Preparationmentioning
confidence: 90%
“…The swelling ratio of UHMWPE is a significant parameter to characterize its swelling behavior. In our previous study, 26 it was observed that the swelling ratio of UHMWPE could achieve 1.53 when it was swollen for 10 min in 300 wt% decalin at 100 C. The determination of swelling temperature and swelling time is indispensable to reflect the swelling behavior of UHMWPE. In order to demonstrate more excellent swelling property, increasing swelling temperature is a feasible and effective method.…”
Section: Swelling Effect Of Uhmwpementioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Pre-swelling of UHMWPE in a solvent, such as decalin, prior to spinning in paraffin oil has been shown to significantly improve the properties of the resulting fibers. 16 Recently, olive oil was blended with decalin and used to pre-swell UHMWPE particles for enhanced polymer chain disentanglement preceding fiber spinning with paraffin oil, which resulted in 24% and 32% increases in tenacity and tensile modulus respectively. 17 Avoiding petrochemical solvents altogether can be accomplished by using orange terpenes, a food-grade biosolvent derived from orange peel waste, which was first demonstrated by Abdul Waqar Rajput in a 2013 dissertation and two subsequent publications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the tensile strength of UHMWPE fibers, it is crucial for improving the fluidity of UHMWPE during processing. The main methods of flow modification include low-viscosity polyolefin blending modification, 11,[14][15][16] lubricant blending modification, 17,18 solution system regulation, [19][20][21] and other modification methods. 7,22,23 Stearic acid (SA) is a popular fatty acid and a common lubricant, 24 applying in various polymer systems with the advantages of low cost and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%